Determination of Listeria monocytogenes and Serotypes in Modified Atmosphere Packed Ground and Cubed Beef Samples - Adem Özkiraz; Ali Gücükoğlu (Turkish Journal of Agriculture: Food Science and Technology)
This study was conducted to determine the Listeria monocytogenes’s presence, serotypes and resistance against various antibiotics in modified atmosphere packaged (MAP) ground and cubed beef samples. Five of ground (5/50-10%) and 3 of cubed beef samples (3/50-6%) were identified as L. monocytogenes positive in MAP samples. Eleven L. monocytogenes isolates that obtained from samples being investigated in term of hlyA gene by PCR method have verified that this gene (100%). In serotyping results, 3 of 8 isolate that obtained from MAP ground beef samples were 1/2a, the other 3 isolate was 1/2b and the remaining 2 isolate was 4b. Also, 1 of 3 isolate that obtained from MAP cubed beef samples were 1/2b, the other one isolate was 1/2c and the last one was 4b. One isolate against (9%) ampicillin, 2 isolate against (18.2%) chloramphenicol, 3 isolate against (27.2%) erythromycin, 4 isolate against (36.3%) oxytetracycline and 4 isolate against (36.3%) penicillin G, 6 isolate against (54.5%) tetracycline and 3 isolate against (27.2%) vancomycin was resistant in 11 L. monocytogenes isolates that confirmed by PCR. The L. monocytogenes isolates were found to be resistant to one or more antibiotics in antibiotic-resistance test results. In conclusion, applying of national residue monitoring program by official authority for prevention of intensive antibiotic use in order to prevent the development of resistant strains to antibiotics has great importance.